The problem of excess of body mass among children and adolescents from rural community of the Podkarpacie region - Rabiasz, Renata; Jarosz, Mirosław J. (Polish Journal of Public Health, 2010)
Introduction. During the last two decades the number of children and adolescents afflicted with overweight or obesity increases permanently all over the world. Mostly, it is an alimentary obesity caused by increased consumption of food and lack of physical activity. Obesity is a state of pathological increase of fatty tissue in a human organism. Aim. The aim of the study was to assess the frequency of overweight and obesity among children and adolescents living in rural communities. Material and methods. The study encompassed children aged seven and adolescents aged fourteen. Together 113 persons (49 girls and 56 boys) have been examined. Height and weight were measured and the Body Mass Index (BMI) – Quetelet’s Index – was calculated. Next, the BMI was converted into a centile scale by age and sex. That scale had been elaborated by Palczewska and Niedzwiecka in order to assess somatic development of the Warsaw children. The results of the research were presented in the form of amount and percentage. For qualitative features disjointed for detecting the existence of differences among the compared groups, homogeneity χ2 with Yates’ correction test was used. Five percent of the inference error was assumed and related to it the significance level of p<0.05 indicating the existence of statistically significant differences. Results. The study revealed that in 7 cases (13.1%) seven-year-old children were afflicted with overweight or obesity. The excess of body mass in adolescents aged 14 concerned one girl (1.9%) only, whereas it did not concern boys. Conclusions. The study did not show a common preva-lence of overweight and obesity in the examined population.